On some aspects of the noise propagation from supersonic aircraft - Lilley, G. M.; Westley, R.; Yates, A. H.; Busing, J. R. (College of Aeronautics, Cranfield, 1953)
The noise problem associated with an aircraft flying at supersonic speeds is shown to depend primarily on the shock wave pattern formed by the aircraft. The noise intensity received by a ground observer from a supersonic aircraft flying at high as well as low altitudes, is shown to be high although it is of a transient nature. Continues…